A verdade em Hegel e Marx - Novelli, Pedro Geraldo Aparecido [UNESP] (My University, 2013)
What is truth? Is there a single truth or many? Is it absolute or relative? Hegel and Marx give some answers through their works. he hegelian and marxist outstanding guide themselves by the dialectical approach according to the singular understanding of each one. Yet, in Hegel as much as in Marx truth has to be seen in the relation between the subject and the object. Both of them make the efort to solve the dichotomy established by other tendencies about the subject and the object. he concept of process is central in their thought and this points at the historical essence of reality. However, it is plain that such a solution can only come out by the passage of the subject to the object (Hegel) and the other way around (Marx). In this way truth in Hegel and Marx has to be understood as an ongoing making process granting the exercise of freedom (Hegel) and an essentially social activity (Marx).

O que é a verdade? Há uma verdade ou muitas? A verdade é absoluta ou relativa? Hegel e Marx proporcionam através de suas obras respostas a essas questões. As posições hegeliana e marxista orientam-se pela abordagem dialética segundo a compreensão de cada um. Tanto em Hegel quanto em Marx a verdade situa-se na relação sujeito-objeto. O esforço de ambos é resolver a dicotomia sujeito-objeto através do conceito de processo que remete à historicidade do real. No entanto, ica evidente neles que a resolução não se realiza senão através de passagem do sujeito pelo objeto (Hegel) e do objeto pelo sujeito (Marx). Desse modo a verdade em Hegel e em Marx deve ser compreendida como uma construção contínua enquanto exercício da liberdade (Hegel) e atividade eminentemente social (Marx).
The truth in hegel and in marx
Keywords: Hegel; Marx; Verdade